Shrimp Plasma CREG Is a Hemocyte Activation Factor - Huang, Zhiqi; Yang, Peng; Wang, Fan (Frontiers in Immunology, 2021)
Cytokines are a class of immunoregulatory proteins that are secreted by cells. Although vertebrate cytokine, especially mammalian cytokine has been well studied for past decades. Much less attention has been paid to invertebrate so that only some cytokines have been identified in invertebrates. We have chosen Peaneus vannamei as a model to explore novel invertebrate cytokines. To achieve this, we previously purified shrimp plasma low abundance proteins and identified more than 400 proteins with proteomics analyses. In this study, a CREG (cellular repressor of E1A-stimulated genes)-like protein, which is highly conserved from Drosophila melanogaster to Homo sapiens, was further characterized in shrimp plasma. We found that shrimp plasma CREG was a glycoprotein which was strongly induced in hemolymph at 8 hours post LPS injection. Further function experiment unveiled that recombinant shrimp CREG protein injection significantly increased phagocytic hemocyte and lysosome-high hemocyte proportion in hemolymph. After that, hemocytes from rEGFP and rCREG protein injected shrimps were subjected to transcriptome analyses, which revealed that shrimp CREG protein could comprehensively promote hemocytes maturation and activation. Taken together, our data clearly indicated that shrimp plasma CREG protein is a novel hemocyte activation factor, which is probably a conserved myeloid cell lineage activation factor from invertebrate to vertebrate.